Chitosan-based hydrogel optical fiber material and preparation method and application thereof

By modifying the combination of chitosan and acrylamide and polyacrylamide, chitosan-based hydrogel optical fiber material was prepared, which solved the problems of poor biocompatibility and insufficient stability in the brain-computer interface, and achieved the combination of high optical performance and biocompatibility.

CN119219848BActive Publication Date: 2025-04-22BEIJING NORMAL UNIV AT ZHUHAI
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411321995.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-04-22
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

In the existing brain-computer interface technology, metal microelectrodes are prone to cause mechanical damage and toxic effects on brain tissue during implantation and use, and have poor stability, affecting their application effect.

Method used

Methacrylic anhydride is used to modify chitosan, combine acrylamide and polyacrylamide, hydrogel fibers are prepared by ultraviolet irradiation, and polyacrylamide solution is wrapped to prepare chitosan-based hydrogel optical fiber materials with good biocompatible and excellent optical properties.

Benefits of technology

It improves the stability and optical properties of hydrogel optical fibers, enhances its biocompatibility and biodegradability, and solves the problems of poor biocompatibility and insufficient stability in traditional brain-computer interface technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219848B_ABST
    Figure CN119219848B_ABST
Patent Text Reader

Abstract

The present invention proposes a chitosan-based hydrogel optical fiber material and a preparation method and application thereof, belonging to the technical field of composite materials. The present invention uses methacrylic anhydride to modify chitosan to obtain a matrix solution of hydrogel optical fiber, enhances the reaction performance of chitosan, mixes the modified chitosan with acrylamide, obtains hydrogel fiber by ultraviolet irradiation, and then wraps the polyacrylamide solution, uses chitosan with a high refractive index as the fiber core, and acrylamide with excellent mechanical properties as the cladding layer, effectively avoiding the problem of large light loss caused by insufficient refractive index of most hydrogels, improving the optical performance of hydrogel optical fiber, and using the prepared chitosan-based hydrogel as an optical fiber material to improve the biocompatibility and biodegradability of brain-computer interface, and the preparation method is simple and easy to operate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a chitosan-based hydrogel optical fiber material and a preparation method and application thereof. Background Art

[0002] With the development of science and technology, brain-computer interface technology has made rapid progress and has gradually become one of the most active research directions in the current field of neural engineering (Wolpaw, 2007; Konrad & Shanks, 2010). Its application fields have gradually expanded, showing great application potential in the fields of biomedicine, neurorehabilitation and intelligent education. Brain-computer interface is a technology that achieves information interaction and functional integration by establishing a direct connection pathway between human or animal brain nerves and external devices. Brain tissue is soft and fragile. The metal microelectrodes that make up the traditional brain-computer interface may cause mechanical damage to the brain tissue during implantation, and the electrodes are prone to displacement or detachment during use, thereby affecting their stability. At the same time, metal microelectrodes may have toxic effects on the surrounding neural tissue. After the metal electrodes are implanted in the organism, it is easy for glial cells to wrap the electrode surface, hindering the contact between the electrode and the nerve, resulting in a decrease in the performance of the neural electrode. Therefore, it is very necessary to find a method to realize brain-computer interface technology without implanting electrodes.

[0003] After years of research, researchers have discovered that implanted optical fibers are small in size and convenient for simultaneously recording signals from multiple brain regions. Brain-computer interfaces can be combined with optogenetics, using optical transmission devices as a window for interacting with the brain.

[0004] Compared with traditional silica-based and glass optical fibers, hydrogels have attracted extensive attention from researchers due to their good biocompatibility and biodegradability (Jing Z et al. 2019; Seo JW et al. 2021). However, due to the poor mechanical properties and stability of hydrogels, and the fact that the refractive index of most hydrogels is not enough to effectively guide the light in the fiber core, it leads to considerable light loss, which limits its further application (HUANG S&FU X, 2010). To solve this problem, scholars have proposed the idea of ​​combining synthetic polymers and natural polymers to prepare hydrogels with comprehensive properties. The Yetisen group (Ali-KYetisen et al. 2017) developed a hydrogel optical fiber with a poly(acrylamide-co-(ethylene glycol) diacrylate) P(AMco-PEGDA) core and a calcium alginate cladding, with 3-(acrylamide)-phenylboronic acid molecules covalently incorporated into the core, and the concentration change of glucose was detected by the change of the transmitted light intensity of the hydrogel optical fiber. To prepare hydrogel optical fibers with good light transmission performance, it is usually necessary to prepare a core-sheath structure, and the refractive index of the inner core is required to be larger than that of the outer cladding to form the conditions for total reflection. Chitosan, as a substance widely present in nature, is the only alkaline polysaccharide among natural polysaccharides. It is non-toxic, cell-affinity and biodegradable. Due to its good biocompatibility and easy physical and chemical modification and hydrophilic structure (rich in amino and hydroxyl groups), it is widely used by researchers in the preparation of hydrogels. In addition, the refractive index of chitosan is 1.7, which is very suitable for the preparation of hydrogel cores. Shen Yi's research group modified chitosan with methacrylic anhydride to develop a photocurable bio-ink with good biocompatibility. In summary, the further development of chitosan-based hydrogel optical fibers will help solve the current problems of poor biocompatibility and poor stability in brain-computer interfaces.

[0005] Although researchers have developed a variety of methods such as electrospinning, 3D printing, and microfluidic processing (Wang Y, et al. 2017) to produce hydrogel fibers, it is still a challenge to synthesize a hydrogel fiber with good biocompatibility and high optical properties. Therefore, the development of a chitosan-based hydrogel fiber with good biocompatibility and excellent optical properties is of great value to further expand the application field of hydrogels and the development of optogenetics and brain-computer interface technology. Summary of the invention

[0006] In order to solve the current problems of poor biocompatibility and instability of brain-computer interfaces, the present invention proposes a chitosan-based hydrogel optical fiber material and a preparation method and application thereof. Chitosan is modified by using methacrylic anhydride to enhance its reaction performance to obtain modified chitosan, and then the modified chitosan is mixed with acrylamide, and hydrogel fibers are obtained after ultraviolet light irradiation. Subsequently, polyacrylamide solution is wrapped to obtain chitosan-based hydrogel optical fibers with good biocompatibility and excellent optical properties.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] One of the technical solutions of the present invention:

[0009] A method for preparing a chitosan-based hydrogel optical fiber material comprises modifying chitosan with methacrylic anhydride, mixing the modified chitosan with acrylamide, irradiating the mixture with ultraviolet light to obtain hydrogel fibers, and then wrapping the fibers with a polyacrylamide solution to obtain the chitosan-based hydrogel optical fiber material.

[0010] Further, the following steps are included:

[0011] (1) dissolving chitosan in an acetic acid solution and heating it, then dropping a methacrylic anhydride solution, adding a saturated sodium bicarbonate solution to neutralize after the reaction is completed, dialyzing, and freeze-drying to obtain modified chitosan;

[0012] (2) dissolving the modified chitosan, acrylamide and ammonium persulfate in water to obtain a mixed solution, stirring the mixed solution for reaction and ultrasonicating the mixed solution to obtain a hydrogel monomer solution;

[0013] (3) injecting the hydrogel monomer solution into a material tube and injecting it into a gel under ultraviolet light to obtain a hydrogel fiber core;

[0014] (4) Immersing the hydrogel fiber core in a polyacrylamide solution, and taking it out to obtain the chitosan-based hydrogel optical fiber material.

[0015] Furthermore, in step (1), the molar ratio of methacrylic anhydride to chitosan is (0.05-0.5):1, the heating temperature is 50-70°C, and the heating time is 4-6h.

[0016] Furthermore, in step (1), the concentration of the acetic acid solution is 0.5wt% to 2.0wt%, and chitosan is dissolved in the acetic acid solution so that the concentration of chitosan in the mixed solution is 0.5wt% to 2.0wt%.

[0017] Furthermore, in step (1), the molecular weight of the dialysis bag for dialysis is 5000-10000 Da, the dialysis time is 36-72 h, and the freeze-drying time is 36-72 h.

[0018] Furthermore, in step (2), in the mixed solution, the concentration of modified chitosan is 1.0wt% to 4.0wt%, the concentration of acrylamide is 5wt% to 15wt%, and the concentration of ammonium persulfate is 0.1wt% to 0.5wt%.

[0019] Furthermore, in step (2), the stirring reaction conditions are 400-600 rpm and the time is 20-40 min; the frequency of the ultrasound is 30-50 Hz and the time is 20-40 min.

[0020] Furthermore, in step (3), the hydrogel monomer solution is injected into the material tube using a syringe, and gelled under ultraviolet light, and then the outer layer of the material tube is torn open to obtain the hydrogel fiber core.

[0021] Furthermore, the material tube is a polytetrafluoroethylene material tube with a diameter of 1 to 2 mm; the wavelength of the ultraviolet light is 360 to 450 nm, and the irradiation time is 0.5 to 2 hours.

[0022] Furthermore, in step (4), the polyacrylamide solution is prepared by dissolving acrylamide, an initiator, and a cross-linking agent in water, and adding an accelerator.

[0023] Furthermore, in the polyacrylamide solution, the concentration of acrylamide is 5wt% to 20wt%, the concentration of the initiator is 0.1wt% to 0.2wt%, and the concentration of the crosslinking agent is 0.01wt% to 0.10wt%.

[0024] Furthermore, the initiator is ammonium persulfate, the cross-linking agent is N,N'-methylenebisacrylamide, and the accelerator is N,N,N,N-tetramethylethylenediamine.

[0025] Furthermore, in step (4), the hydrogel fiber core is immersed in a polyacrylamide solution for a reaction time of 1 to 3 minutes, and the diameter of the obtained chitosan-based hydrogel optical fiber material is 600 to 1200 μm.

[0026] The second technical solution of the present invention:

[0027] A chitosan-based hydrogel optical fiber material prepared by the preparation method.

[0028] The third technical solution of the present invention:

[0029] The application of the chitosan-based hydrogel optical fiber material in brain-computer interface.

[0030] Compared with the prior art, the present invention has the following advantages and technical effects:

[0031] (1) The present invention uses methacrylic anhydride to modify chitosan to obtain a matrix solution of hydrogel optical fiber, thereby enhancing the reaction performance of chitosan, obtaining more stable mechanical properties, and enhancing the stability of the hydrogel optical fiber; and uses chitosan with a high refractive index as the fiber core and acrylamide with excellent mechanical properties as the cladding layer, effectively avoiding the problem of large light loss caused by insufficient refractive index of most hydrogels, thereby improving the optical performance of the hydrogel optical fiber.

[0032] (2) The present invention uses chitosan-based hydrogel as the optical fiber material, which can improve the biocompatibility and biodegradability of the brain-computer interface, and the preparation method is simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0034] Figure 1 The invention relates to the reaction process between methacrylic anhydride and chitosan in the preparation method of chitosan-based hydrogel optical fiber material;

[0035] Figure 2 The infrared spectra of chitosan before and after modification in Example 1;

[0036] Figure 3 These are morphological images of the chitosan-based hydrogel optical fiber material prepared in Example 1 at different magnifications, a being magnified 500 times, and b being magnified 100 times. DETAILED DESCRIPTION

[0037] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0038] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0039] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0040] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0041] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0042] The present invention provides a method for preparing a chitosan-based hydrogel optical fiber material, wherein chitosan is modified by methacrylic anhydride (the reaction process of methacrylic anhydride and chitosan is shown in FIG. Figure 1 ), the modified chitosan is mixed with acrylamide, and the hydrogel fiber is obtained by ultraviolet irradiation, and then the polyacrylamide solution is wrapped to obtain the chitosan-based hydrogel optical fiber material, which more specifically includes the following steps:

[0043] (1) dissolving chitosan in an acetic acid solution and heating it, then dropping a methacrylic anhydride solution, adding a saturated sodium bicarbonate solution to neutralize after the reaction is completed, dialyzing, and freeze-drying to obtain modified chitosan;

[0044] (2) dissolving the modified chitosan, acrylamide and ammonium persulfate in water to obtain a mixed solution, stirring the mixed solution for reaction and ultrasonicating the mixed solution to obtain a hydrogel monomer solution;

[0045] (3) injecting the hydrogel monomer solution into a gel under ultraviolet light to obtain a hydrogel fiber core;

[0046] (4) Immersing the hydrogel fiber core in a polyacrylamide solution, and taking it out to obtain a chitosan-based hydrogel optical fiber material with a core-sheath structure.

[0047] In step (1) of a preferred embodiment of the present invention, the molar ratio of methacrylic anhydride to chitosan is (0.05-0.5):1, the heating temperature is 50-70°C, and the heating time is 4-6h.

[0048] In step (1) of a preferred embodiment of the present invention, the concentration of the acetic acid solution is 0.5 wt% to 2.0 wt%, and chitosan is dissolved in the acetic acid solution so that the concentration of chitosan in the mixed solution is 0.5 wt% to 2.0 wt%.

[0049] In step (1) of the preferred embodiment of the present invention, the molecular weight of the dialysis bag for dialysis is 5000-10000 Da, the dialysis time is 36-72 h, and the freeze-drying time is 36-72 h.

[0050] In step (2) of a preferred embodiment of the present invention, in the mixed solution, the concentration of modified chitosan is 1.0 wt% to 4.0 wt%, the concentration of acrylamide is 5 wt% to 15 wt%, and the concentration of ammonium persulfate is 0.1 wt% to 0.5 wt%.

[0051] In step (2) of a preferred embodiment of the present invention, the stirring reaction conditions are 400-600 rpm and the time is 20-40 min; the frequency of the ultrasound is 30-50 Hz and the time is 20-40 min.

[0052] In step (3) of the preferred embodiment of the present invention, the hydrogel monomer solution is injected into the material tube using a syringe, and gelled under ultraviolet light, and then the outer layer of the material tube is torn open to obtain the hydrogel fiber core.

[0053] Preferably, the material tube is a polytetrafluoroethylene material tube with a diameter of 1 to 2 mm; the wavelength of the ultraviolet light is 360 to 450 nm, and the irradiation time is 0.5 to 2 h.

[0054] In step (4) of the preferred embodiment of the present invention, the polyacrylamide solution is prepared by mixing acrylamide, an initiator, and a cross-linking agent, dissolving them in water, and adding an accelerator.

[0055] Preferably, the concentration of acrylamide in the polyacrylamide solution is 5wt% to 20wt%, the concentration of the initiator is 0.1wt% to 0.2wt%, and the concentration of the crosslinking agent is 0.01wt% to 0.10wt%.

[0056] Preferably, the initiator is ammonium persulfate, the cross-linking agent is N,N-methylenebisacrylamide, and the accelerator is N,N,N,N-tetramethylethylenediamine.

[0057] In step (4) of the preferred embodiment of the present invention, the hydrogel fiber core is immersed in a polyacrylamide solution for a reaction time of 1 to 3 minutes, and the diameter of the prepared chitosan-based hydrogel optical fiber material is 600 to 1200 μm.

[0058] The embodiment of the present invention also provides a chitosan-based hydrogel optical fiber material prepared by the preparation method.

[0059] All raw materials in the examples of the present invention are commercially available.

[0060] The molar mass of the methacrylic anhydride solution used in the embodiment of the present invention is 154.17 g / mol, the deacetylation degree of chitosan is 95%, and the molar mass of the repeating unit is about 163 g / mol.

[0061] The technical solution of the present invention is further illustrated by the following embodiments.

[0062] Example 1

[0063] (1) 1.0 g (0.006 mol) of chitosan was dissolved in 100 mL of 1 wt% acetic acid solution, heated to 60° C. in an oil bath, and then 0.10 g of methacrylic anhydride solution (0.0006 mol) was added dropwise. The reaction was continued for 6 h. After that, the reaction solution was neutralized with a saturated sodium bicarbonate solution and dialyzed in distilled water with a dialysis bag (molecular weight 7000 Da) for 48 h. Finally, the dialyzed solution was pretreated with liquid nitrogen and freeze-dried in a freeze dryer for 48 h to obtain modified chitosan.

[0064] (2) mixing the modified chitosan obtained in step (1) with acrylamide and ammonium persulfate in 4 mL of pure water, wherein the concentration of the modified chitosan is 2.0 wt %, the concentration of acrylamide is 10 wt %, and the concentration of ammonium persulfate is 0.2 wt %, stirring the mixture to make it uniform, letting it stand for 30 min, and ultrasonicating the mixture for 30 min to obtain a hydrogel monomer solution;

[0065] (3) placing the hydrogel monomer solution obtained in step (2) into a syringe, injecting the hydrogel monomer solution into a polytetrafluoroethylene material tube with an inner diameter of 1.6 mm using the syringe, and forming a gel under 395 nm ultraviolet light for 60 minutes, then using scissors to cut the material tube open and tear open the polytetrafluoroethylene material tube on the outer layer of the hydrogel fiber core to obtain a hydrogel fiber core;

[0066] (4) acrylamide (2 g, 10 wt %, refers to the concentration in pure water), ammonium persulfate (32 mg, 0.16 wt %), and N,N'-methylenebisacrylamide (12 mg, 0.06 wt %) were placed in 20 g of pure water solution and stirred evenly, and then 20 μL of N,N,N,N-tetramethylethylenediamine was added as an accelerator to obtain a 10 wt % polyacrylamide solution;

[0067] The hydrogel core obtained in step (3) is uniformly immersed in the polyacrylamide solution for 3 minutes and then taken out to obtain a chitosan-based hydrogel optical fiber material.

[0068] The infrared spectra of chitosan before and after modification in step (1) of Example 1 are shown in Figure 2 In the figure, CHI represents chitosan before modification, and MA:CHI=0.1 represents chitosan after modification. Figure 2 It can be seen that after modification, chitosan showed an obvious C=C absorption peak, proving that the modification was successful.

[0069] The morphology of the chitosan-based hydrogel optical fiber material prepared in Example 1 of the present invention at different magnifications is as follows: Figure 3 As shown, a is magnified 500 times, b is magnified 100 times, from Figure 3 It can be seen that the prepared hydrogel optical fiber has an obvious core-shell structure. The part marked with a ruler is the shell layer, which has a larger and sparser morphology, and the inside is the core layer, which has a denser morphology. The shell layer is about 60μm thick, and the diameter of the hydrogel optical fiber is about 800μm.

[0070] The chitosan-based hydrogel optical fiber material prepared in this example was subjected to an optical performance test experiment. The optical loss of the hydrogel optical fiber was tested using an insertion test method, and the optical loss of the hydrogel optical fiber was measured to be 11.8 dB.

[0071] Example 2

[0072] (1) 0.5 g (0.003 mol) of chitosan was dissolved in 100 mL of 1 wt% acetic acid solution, heated to 70° C. in an oil bath, and then 0.24 g (0.0015 mol) of methacrylic anhydride solution was added dropwise. The reaction was continued for 4 h. After that, the reaction solution was neutralized with a saturated sodium bicarbonate solution and dialyzed in distilled water with a dialysis bag (molecular weight 5000 Da) for 72 h. Finally, the dialyzed solution was pretreated with liquid nitrogen and freeze-dried in a freeze dryer for 60 h to obtain modified chitosan;

[0073] (2) mixing the modified chitosan obtained in step (1) with acrylamide and ammonium persulfate in 4 mL of pure water, wherein the concentration of the modified chitosan is 1.0 wt %, the concentration of acrylamide is 15 wt %, and the concentration of ammonium persulfate is 0.1 wt %, stirring the mixture to make it uniform, letting it stand for 30 min, and ultrasonicating it for 30 min to obtain a hydrogel monomer solution;

[0074] (3) placing the hydrogel monomer solution obtained in step (2) into a syringe, injecting the hydrogel monomer solution into a polytetrafluoroethylene material tube with an inner diameter of 1 mm using the syringe, and irradiating the material tube with 360 nm ultraviolet light for 120 min to form a gel, then using scissors to cut the material tube open and tear open the polytetrafluoroethylene material tube on the outer layer of the hydrogel fiber core to obtain the hydrogel fiber core;

[0075] (4) acrylamide (2 g, 10 wt %, refers to the concentration in pure water), ammonium persulfate (40 mg, 0.2 wt %), and N,N'-methylenebisacrylamide (12 mg, 0.06 wt %) were placed in 20 g of pure water solution and stirred evenly, and then 10 μL of N,N,N,N-tetramethylethylenediamine was added as an accelerator to obtain a 10 wt % polyacrylamide solution;

[0076] The hydrogel core obtained in step (3) is uniformly immersed in the polyacrylamide solution for 3 minutes and then taken out to obtain a chitosan-based hydrogel optical fiber material.

[0077] The chitosan-based hydrogel optical fiber material prepared in this example was subjected to an optical performance test experiment. The optical loss of the hydrogel optical fiber was tested using an insertion test method, and the optical loss of the hydrogel optical fiber was measured to be 12.3 dB.

[0078] Example 3

[0079] (1) 2.0 g (0.012 mol) of chitosan was dissolved in 100 mL of 2 wt% acetic acid solution, heated to 50° C. in an oil bath, and then 0.1 g (0.0006 mol) of methacrylic anhydride solution was added dropwise. The reaction was continued for 6 h. After that, the reaction solution was neutralized with a saturated sodium bicarbonate solution and dialyzed in distilled water with a dialysis bag (molecular weight 10000 Da) for 36 h. Finally, the dialyzed solution was pretreated with liquid nitrogen and freeze-dried in a freeze dryer for 72 h to obtain modified chitosan;

[0080] (2) mixing the modified chitosan obtained in step (1) with acrylamide and ammonium persulfate in 4 mL of pure water, wherein the concentration of the modified chitosan is 3.0 wt %, the concentration of acrylamide is 20 wt %, and the concentration of ammonium persulfate is 0.4 wt %, stirring the mixture to make it uniform, letting it stand for 30 min, and ultrasonicating the mixture for 30 min to obtain a hydrogel monomer solution;

[0081] (3) placing the hydrogel monomer solution obtained in step (2) into a syringe, injecting the hydrogel monomer solution into a polytetrafluoroethylene material tube with an inner diameter of 2 mm using the syringe, and irradiating the material tube with 395 nm ultraviolet light for 120 min to form a gel, then using scissors to cut the material tube open and tear open the polytetrafluoroethylene material tube on the outer layer of the hydrogel fiber core to obtain a hydrogel fiber core;

[0082] (4) acrylamide (4 g, 20 wt %, refers to the concentration in pure water), ammonium persulfate (20 mg, 0.1 wt %), and N,N'-methylenebisacrylamide (20 mg, 0.1 wt %) were placed in 20 g of pure water solution and stirred evenly, and then 30 μL of N,N,N,N-tetramethylethylenediamine was added as an accelerator to obtain a 20 wt % polyacrylamide solution;

[0083] The hydrogel core obtained in step (3) is uniformly immersed in the polyacrylamide solution for 3 minutes and then taken out to obtain a chitosan-based hydrogel optical fiber material.

[0084] The chitosan-based hydrogel optical fiber material prepared in this example was subjected to an optical performance test experiment. The optical loss of the hydrogel optical fiber was tested using an insertion test method, and the optical loss of the hydrogel optical fiber was measured to be 15.2 dB.

[0085] Example 4

[0086] (1) 1.0 g (0.006 mol) of chitosan was dissolved in 100 mL of 1 wt% acetic acid solution, heated to 60° C. in an oil bath, and then 0.096 g (0.0006 mol) of methacrylic anhydride solution was added dropwise. The reaction was continued for 6 h. After that, the reaction solution was neutralized with a saturated sodium bicarbonate solution and dialyzed in distilled water with a dialysis bag (molecular weight 7000 Da) for 48 h. Finally, the dialyzed solution was pretreated with liquid nitrogen and placed in a freeze dryer for 48 h to obtain modified chitosan;

[0087] (2) mixing the modified chitosan obtained in step (1) with acrylamide and ammonium persulfate in 4 mL of pure water, wherein the concentration of the modified chitosan is 1.0 wt %, the concentration of acrylamide is 10 wt %, and the concentration of ammonium persulfate is 0.2 wt %, stirring the mixture to make it uniform, letting it stand for 30 min, and ultrasonicating the mixture for 30 min to obtain a hydrogel monomer solution;

[0088] (3) placing the hydrogel monomer solution obtained in step (2) into a syringe, injecting the hydrogel monomer solution into a polytetrafluoroethylene material tube with an inner diameter of 1.6 mm using the syringe, and irradiating the material tube with 450 nm ultraviolet light for 30 minutes to form a gel, then using scissors to cut the material tube open and tear open the polytetrafluoroethylene material tube on the outer layer of the hydrogel fiber core to obtain a hydrogel fiber core;

[0089] (4) acrylamide (2 g, 10 wt %, refers to the concentration in pure water), ammonium persulfate (32 mg, 0.16 wt %), and N,N'-methylenebisacrylamide (12 mg, 0.06 wt %) were placed in 20 g of pure water solution and stirred evenly, and then 20 μL of N,N,N,N-tetramethylethylenediamine was added as an accelerator to obtain a 10 wt % polyacrylamide solution;

[0090] The hydrogel core obtained in step (3) is uniformly immersed in the polyacrylamide solution for 3 minutes and then taken out to obtain a chitosan-based hydrogel optical fiber material.

[0091] The chitosan-based hydrogel optical fiber material prepared in this example was subjected to an optical performance test experiment. The optical loss of the hydrogel optical fiber was tested using an insertion test method, and the optical loss of the hydrogel optical fiber was measured to be 12.6 dB.

[0092] Example 5

[0093] (1) 1.0 g (0.006 mol) of chitosan was dissolved in 100 mL of 1 wt% acetic acid solution, heated to 60° C. in an oil bath, and then 0.096 g (0.0006 mol) of methacrylic anhydride solution was added dropwise. The reaction was continued for 6 h. After that, the reaction solution was neutralized with a saturated sodium bicarbonate solution and dialyzed in distilled water with a dialysis bag (molecular weight 7000 Da) for 48 h. Finally, the dialyzed solution was pretreated with liquid nitrogen and placed in a freeze dryer for 48 h to obtain modified chitosan;

[0094] (2) mixing the modified chitosan obtained in step (1) with acrylamide and ammonium persulfate in 4 mL of pure water, wherein the concentration of the modified chitosan is 4.0 wt %, the concentration of acrylamide is 10 wt %, and the concentration of ammonium persulfate is 0.2 wt %, stirring the mixture to make it uniform, letting it stand for 30 min, and ultrasonicating the mixture for 30 min to obtain a hydrogel monomer solution;

[0095] (3) placing the hydrogel monomer solution obtained in step (2) into a syringe, injecting the hydrogel monomer solution into a polytetrafluoroethylene material tube with an inner diameter of 1.6 mm using the syringe, and forming a gel under 395 nm ultraviolet light for 60 minutes, then using scissors to cut the material tube open and tear open the polytetrafluoroethylene material tube on the outer layer of the hydrogel fiber core to obtain a hydrogel fiber core;

[0096] (4) acrylamide (2 g, 10 wt %, refers to the concentration in pure water), ammonium persulfate (32 mg, 0.16 wt %), and N,N'-methylenebisacrylamide (12 mg, 0.06 wt %) were placed in 20 g of pure water solution and stirred evenly, and then 20 μL of N,N,N,N-tetramethylethylenediamine was added as an accelerator to obtain a 10 wt % polyacrylamide solution;

[0097] The hydrogel core obtained in step (3) is uniformly immersed in the polyacrylamide solution for 3 minutes and then taken out to obtain a chitosan-based hydrogel optical fiber material.

[0098] The chitosan-based hydrogel optical fiber material prepared in this example was subjected to an optical performance test experiment. The optical loss of the hydrogel optical fiber was tested using an insertion test method, and the optical loss of the hydrogel optical fiber was measured to be 16.3 dB.

[0099] Example 6

[0100] (1) 1.0 g (0.006 mol) of chitosan was dissolved in 100 mL of 1 wt% acetic acid solution, heated to 60° C. in an oil bath, and then 0.096 g (0.0006 mol) of methacrylic anhydride solution was added dropwise. The reaction was continued for 6 h. After that, the reaction solution was neutralized with a saturated sodium bicarbonate solution and dialyzed in distilled water with a dialysis bag (molecular weight 7000 Da) for 48 h. Finally, the dialyzed solution was pretreated with liquid nitrogen and placed in a freeze dryer for 48 h to obtain modified chitosan;

[0101] (2) mixing the modified chitosan obtained in step (1) with acrylamide and ammonium persulfate in 4 mL of pure water, wherein the concentration of the modified chitosan is 2.0 wt %, the concentration of acrylamide is 5 wt %, and the concentration of ammonium persulfate is 0.2 wt %, stirring the mixture to make it uniform, letting it stand for 30 min, and ultrasonicating the mixture for 30 min to obtain a hydrogel monomer solution;

[0102] (3) placing the hydrogel monomer solution obtained in step (2) into a syringe, injecting the hydrogel monomer solution into a polytetrafluoroethylene material tube with an inner diameter of 1.6 mm using the syringe, and forming a gel under 395 nm ultraviolet light for 60 minutes, then using scissors to cut the material tube open and tear open the polytetrafluoroethylene material tube on the outer layer of the hydrogel fiber core to obtain a hydrogel fiber core;

[0103] (4) acrylamide (1 g, 5 wt %, referring to the concentration in pure water), ammonium persulfate (32 mg, 0.16 wt %), and N,N'-methylenebisacrylamide (12 mg, 0.06 wt %) were placed in 20 g of pure water solution and stirred evenly, and then 20 μL of N,N,N,N-tetramethylethylenediamine was added as an accelerator to obtain a 5 wt % polyacrylamide solution;

[0104] The hydrogel core obtained in step (3) is uniformly immersed in the polyacrylamide solution for 3 minutes and then taken out to obtain a chitosan-based hydrogel optical fiber material.

[0105] The chitosan-based hydrogel optical fiber material prepared in this example was subjected to an optical performance test experiment. The optical loss of the hydrogel optical fiber was tested using an insertion test method, and the optical loss of the hydrogel optical fiber was measured to be 13.4 dB.

[0106] Example 7

[0107] (1) 1.0 g (0.006 mol) of chitosan was dissolved in 100 mL of 1 wt% acetic acid solution, heated to 60° C. in an oil bath, and then 0.096 g (0.0006 mol) of methacrylic anhydride solution was added dropwise. The reaction was continued for 6 h. After that, the reaction solution was neutralized with a saturated sodium bicarbonate solution and dialyzed in distilled water with a dialysis bag (molecular weight 7000 Da) for 48 h. Finally, the dialyzed solution was pretreated with liquid nitrogen and placed in a freeze dryer for 48 h to obtain modified chitosan;

[0108] (2) mixing the modified chitosan obtained in step (1) with acrylamide and ammonium persulfate in 4 mL of pure water, wherein the concentration of the modified chitosan is 2.0 wt %, the concentration of acrylamide is 20 wt %, and the concentration of ammonium persulfate is 0.2 wt %, stirring the mixture to make it uniform, letting it stand for 30 min, and ultrasonicating the mixture for 30 min to obtain a hydrogel monomer solution;

[0109] (3) placing the hydrogel monomer solution obtained in step (2) into a syringe, injecting the hydrogel monomer solution into a polytetrafluoroethylene material tube with an inner diameter of 1.6 mm using the syringe, and forming a gel under 395 nm ultraviolet light for 60 minutes, then using scissors to cut the material tube open and tear open the polytetrafluoroethylene material tube on the outer layer of the hydrogel fiber core to obtain a hydrogel fiber core;

[0110] (4) acrylamide (4 g, 20 wt %, concentration in pure water), ammonium persulfate (32 mg, 0.16 wt %), and N,N'-methylenebisacrylamide (12 mg, 0.06 wt %) were placed in 20 g of pure water solution and stirred evenly, and then 20 μL of N,N,N,N-tetramethylethylenediamine was added as an accelerator to obtain a 20 wt % polyacrylamide solution;

[0111] The hydrogel core obtained in step (3) is uniformly immersed in the polyacrylamide solution for 3 minutes and then taken out to obtain a chitosan-based hydrogel optical fiber material.

[0112] The chitosan-based hydrogel optical fiber material prepared in this example was subjected to an optical performance test experiment. The optical loss of the hydrogel optical fiber was tested using an insertion test method, and the optical loss of the hydrogel optical fiber was measured to be 16.4 dB.

[0113] It can be seen from Examples 1 to 7 that the present invention uses methacrylic anhydride to modify chitosan to obtain a matrix solution for hydrogel optical fiber, thereby enhancing the reactivity of chitosan, obtaining more stable mechanical properties than single chitosan hydrogel, and enhancing the stability of the hydrogel optical fiber; and using chitosan with a high refractive index as the fiber core and acrylamide with excellent mechanical properties as the cladding layer, effectively avoiding the problem of large light loss caused by insufficient refractive index of most hydrogels, thereby improving the optical performance of the hydrogel optical fiber.

[0114] Specific application examples

[0115] The chitosan-based hydrogel optical fiber material prepared in the example was implanted into the brain of a mouse, and the results showed that the action of the mouse could be controlled by using optical signals.

[0116] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A method for preparing a chitosan-based hydrogel optical fiber material, characterized in that: The following steps are involved: (1) dissolving chitosan in an acetic acid solution and heating it, then dropping a methacrylic anhydride solution, adding a saturated sodium bicarbonate solution to neutralize after the reaction is completed, dialyzing, and freeze-drying to obtain modified chitosan; (2) dissolving the modified chitosan, acrylamide and ammonium persulfate in water to obtain a mixed solution, stirring the mixed solution for reaction and ultrasonicating the mixed solution to obtain a hydrogel monomer solution; (3) injecting the hydrogel monomer solution into a gel under ultraviolet light to obtain hydrogel fibers; (4) Immersing the hydrogel fiber in a polyacrylamide solution, and taking it out to obtain the chitosan-based hydrogel optical fiber material.

2. The method for preparing chitosan-based hydrogel optical fiber material according to claim 1, characterized in that: In step (1), the molar ratio of methacrylic anhydride to chitosan is (0.05-0.5):1, the heating temperature is 50-70°C, and the heating time is 4-6 hours.

3. The method for preparing chitosan-based hydrogel optical fiber material according to claim 1, characterized in that: In step (2), in the mixed solution, the concentration of modified chitosan is 1.0wt% to 4.0wt%, the concentration of acrylamide is 5wt% to 15wt%, and the concentration of ammonium persulfate is 0.1wt% to 0.5wt%.

4. The method for preparing chitosan-based hydrogel optical fiber material according to claim 1, characterized in that: In step (3), the hydrogel monomer solution is injected into the material tube using a syringe, and gelled under ultraviolet light, and then the outer layer of the material tube is torn open to obtain hydrogel fibers.

5. The method for preparing chitosan-based hydrogel optical fiber material according to claim 4, characterized in that: The material tube is a polytetrafluoroethylene material tube with a diameter of 1 to 2 mm; the wavelength of the ultraviolet light is 360 to 450 nm, and the irradiation time is 0.5 to 2 hours.

6. The method for preparing chitosan-based hydrogel optical fiber material according to claim 1, characterized in that: In step (4), the polyacrylamide solution is prepared by mixing acrylamide, an initiator, and a cross-linking agent, dissolving them in water, and adding an accelerator.

7. The method for preparing chitosan-based hydrogel optical fiber material according to claim 6, characterized in that: The concentration of acrylamide in the polyacrylamide solution is 5wt% to 20wt%, the concentration of the initiator is 0.1wt% to 0.2wt%, and the concentration of the crosslinking agent is 0.01wt% to 0.10wt%; The initiator is ammonium persulfate, the cross-linking agent is N,N'-methylenebisacrylamide, and the accelerator is N,N,N,N-tetramethylethylenediamine.

8. A chitosan-based hydrogel optical fiber material prepared by the preparation method according to any one of claims 1 to 7.

9. Application of the chitosan-based hydrogel optical fiber material as claimed in claim 8 in brain-computer interface.

Citation Information

Patent Citations

  • Chitosan hydrogel, and preparation method thereof

    CN110194840A